Inclusive Education as an Ethical and Humanistic Practice from the Perspective of Islamic Educational Philosophy: A Literature Study in the Context of Madrasah Ibtidaiyah - Andriani, Lusi; Vidayanti, Vivit; Rifai, Mohammad Saiful; Khoiriyah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
This study aims to reflect on and reconstruct inclusive education as an ethical–humanistic practice from the perspective of Islamic educational philosophy within the context of Madrasah Ibtidaiyah through a systematic literature study. The research employed content analysis of selected primary and secondary sources, including reputable national and international journal articles, classical Islamic educational texts, and relevant educational policy documents. Literature selection was conducted purposively based on relevance, academic credibility, and recency, while data validity was ensured through source triangulation. The findings formulate a conceptual framework termed Tauhidic Inclusion, which integrates three interrelated dimensions: the vertical dimension (tawhid as a spiritual–ontological foundation of human equality), the horizontal dimension (‘adl as a principle of equitable access and educational justice), and the relational dimension (rahmah as the basis of empathetic and humanistic pedagogy). This framework positions inclusive education not merely as a technical accommodation strategy for learner diversity, but as an ethical and humanistic educational paradigm rooted in Islamic values. Theoretically, this study contributes to the discourse of Islamic education by offering an integrative philosophical model of inclusion that bridges Islamic thought and contemporary inclusion theory. Practically, it provides conceptual guidance for the development of inclusive learning practices, curriculum design, and madrasah culture in Madrasah Ibtidaiyah. This study is limited by its reliance on literature-based analysis and its focus on the primary level of Islamic education. The originality of this research lies in reconstructing inclusive education through an Islamic philosophical lens, integrating classical Islamic scholarship with modern inclusion theory in a manner rarely explored in Indonesian educational literature